Daya Saing Kopi Indonesia di Pasar Internasional dalam 3 Dekade Terakhir - Azizi, Ernes Septina (LP3M Universitas Putra Bangsa, 2023)
Coffee is one of the most important commodities that have an important role in economic growth, especially in supporting the increase of non-oil exports in Indonesia and as a foreign exchange earner. The purpose of this article is to analyze competitiveness of Indonesian coffee in international market in the last 3 decades or during period 1989–2019. Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), X-Model Potential Export Product and Diamond Porter’s is used to analysis competitiveness. The results of the analysis of competitiveness using the RCA method show that not all HS codes for Indonesian coffee and competing countries have a comparative advantage, Indonesian coffee has strong competitiveness for HS code 090111 but has no strong competitive power for other HS codes. The results of the EPD method show that for all HS codes Indonesian coffee and competing countries have a rising star position or have positive appeal and increased market share. The results of the X-Model Potential Export Product method show that Indonesia and competing countries have optimistic coffee market developments for HS code 090111 and have potential market developments for HS codes 090112, 090121, 090122, and 090190. From the results of Porter Diamond's analysis, the results obtained that the State of Indonesia has advantages in terms of condition factors, namely natural resources and has weaknesses in science and technology, human resources and capital resources.